Improving Self-Learning for Deaf Students in SMPLB Through Use of BISINDO Video in Heat and Temperature - Rusilowati, A.; Sulhadi, S.; Purwaningtyas, S. A.; Perwitasari, A. D. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2020)
Deaf students have limitations on the sense of hearing, so to grow self-learning requires special processes and training. The results of the observations at the especialy needs secondary school (Sekolah menengah pertama luar biasa negeri/SMPLB-N-in Indosesia) found that one of the goals of the SMPLB-N Ungaran was to produce graduates who were independent and could live in community life. This study aims to improve the learning independence of SMPLB-N Ungaran students by using BISINDO-based videos. This video is equipped with sign language that makes it easy for students to understand the material being studied. The method used is an experiment with the design of single subject A-B patterns. A is baseline dan B is Intervention. The data analysis technique uses descriptive percentages. BISINDO-based video-assisted learning helps students improve self-learning. The increase in the learning independence of deaf students from the baseline phase to the intervention phase was 2.29 in the high category. The average increase in students’ self-learning is 46.1% for the personal aspects of attributes, 52.4% for the aspect process, and 10.2% for the learning context aspect.